The estimation of Vardenis river’s ecological state by the approaches of EU Water Framework Directiv - V. L. Asatryan (ՀՀ ԳԱԱ հրատ.)
The results of estimation of Vardenis river basin’ water ecological state based on hydrobiological and hydromorphological studies has been presented. Study has been carried out by AQEM methodology which based on the norms of EU WFD. The results of river’ water quality estimation by FBI, BBI, BMWP indices based on data of zoobenthos have been comparatively analyzed and the most reliable index for estimation of water quality based on multihabitat sampling method has been revealed. The results have shown that the most reliable index from 3 implemented for the estimation of Vardenis river water quality is FBI. The scores of indices have shown that water quality of Vardenis river not lower than “good”, at the same time all 3 indices have shown that the best quality is in the middle stream (FBI-1.4, BBI-9, BMWP-133), lower quality in the upper stream (FBI-4.8, BBI-7, BMWP-58) and the worst – in the downstream (FBI-5.35, BBI-4, BMWP-68). This is generally due to differences in anthropogenic impact size in different parts of river as a result of hydromorphological parameters. result of hydromorphological parameters.
Keywords: Biology; Ecology